KEMAMPUAN BERPIKIR KREATIF SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI KECERDASAN INTRAPERSONAL - Diah Risti Oktaviani; Harina Fitriyani (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
This study aims to describe the profile of creative thinking ability of VII grade students in one of the state middle schools in Bantul in solving mathematic problems of planar figure material that have high, medium, low intrapersonal intelligence and to describe the mapping of intrapersonal intelligence of 7th grade students. This research is qualitative research. The research subjects were 6 students of grade VII. The research object is intrapersonal intelligence and creative thinking. The data technique used an intrapersonal intelligence questionnaire, written tests, and interviews. The results showed that students who had high intrapersonal intelligence and were able to fulfill all indicators of creative thinking, namely fluency, competence, and novelty. Meanwhile, students who have low intrapersonal intelligence who are able to fulfill one of the indicators of creative thinking are able to meet one of the indicators of creative thinking